MONETARY CREDIT POLICY OF THE CENTRAL BANK AND ITS MACROECONOMIC SIGNIFICANCE - Murodova Dilnoza Choriyevna (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The article includes the purpose, tasks, strategy and tactics of regulating the activities of commercial banks through the monetary and credit policy instruments carried out by the Central Bank of the Republic of Uzbekistan. It describes the nature of commercial banks, threats affecting their economic security, methods of protection against them, criteria for assessing the economic security of commercial banks